PERAN PENDIDIKAN DAN LINGKUNGAN DALAM MENDUKUNG PERKEMBANGAN BAHASA DAN KOGNITIF ANAK - Yani Novita Sari; Meri Yessari; Rahmides Utami; Alpan Suri; Hafiz Hidayat (STKIP Subang, 2024)
Language and cognitive development is the main foundation in children's learning and social interaction processes. This research explores the contribution of education and environment to language and cognitive development, and offers strategic recommendations for optimizing both factors. This research uses the literature study method to collect secondary data from various relevant sources, such as journals, books and proceedings. The analysis process is carried out in three stages: (1) organizing the literature based on relevant themes, (2) synthesizing information to find connections between the literature, and (3) identifying important data to produce in-depth conclusions about the role of education and the environment in language development and cognition child. This research identifies the significant role of formal education and the family environment in supporting children's language and cognitive development. Findings showed that a curriculum involving language stimulation and cognitive activities significantly improved children's receptive and expressive language abilities. In addition, social interactions with parents, peers, and teachers have been proven to enrich children's cognitive and linguistic development. However, obstacles such as lack of access to quality education, an environment that lacks stimulation, and the impact of uncontrolled use of technology can hinder this development process. This research suggests a collaborative approach between educational institutions, families and communities to create a learning environment that supports children's development in a comprehensive and sustainable manner.